2018
DOI: 10.1155/2018/4128243
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Synthesis of La2O3/GO Nanocomposites in N,N-Dimethylformamide with High Dye Degradation Efficiency

Abstract: La 2 O 3 /graphene oxide (GO) nanocomposites were simply synthesized from commercially available LaCl 3 ⋅7H 2 O and multilayer GO (5-10 layers) in N,N-dimethylformamide (DMF) under reflux condition without extra stabilizer. The characterization results of scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray photoelectron spectrum (XPS) spectroscopies showed that the crystalline La 2 O 3 nanoparticles were successfully attached on the surface of GO. Moreover, the as-prepared nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Arshad et al reported that Ni-doped La 2 O 3 reveals the highest photocatalytic degradation of 99.15% in 30 min . According to He et al, GO-doped La 2 O 3 exhibited a degradation potential for RhB of 63.2% in 15 min …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arshad et al reported that Ni-doped La 2 O 3 reveals the highest photocatalytic degradation of 99.15% in 30 min . According to He et al, GO-doped La 2 O 3 exhibited a degradation potential for RhB of 63.2% in 15 min …”
Section: Introductionmentioning
confidence: 99%
“… 12 According to He et al, GO-doped La 2 O 3 exhibited a degradation potential for RhB of 63.2% in 15 min. 13 …”
Section: Introductionmentioning
confidence: 99%